Ghumi Uttara: A New Music Creation | Ghumi Uttara: Sebuah Karya Musik Baru - Kadek Teddy Mertayasa; Kadek Suartaya (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
The creation of percussion music “Ghumi Uttara” raises the idea of creation that was born from the author's personal experience in playing percussion which identifies Buleleng Regency. This work highlights the processing of the sekatian and lelongoran percussions in Buleleng Regency. The aim is to give a message to the public that the percussion of the Sekatian and the percussion of the Lelongoran are percussions that identify Buleleng Regency which must be preserved and disseminated widely. The method used in the process of creating the musical creation